Development of a GIS-Based Information System for Watershed Monitoring in Mato Grosso, Central Brazil - ZEILHOFER, PETER; LIMA, GILSON ALBERTO; LIMA, ELIANA BEATRIZ RONDON; SANTOS, IVAIRTON MONTEIRO (Pesquisas em Geociências, 2008)
This paper describes the conceptual framework and implementation of a prototype for a GIS-based Information System for Watershed Monitoring and Planning in the state of Mato Grosso, Central Brazil. The system was developed to support the implementation of water resources management policies passed by Brazilian federal and state legislatures in 1997.The first phase of the information system development was focused on database design, to create modules for the storage and pre-processing of diverse environmental data sets and for georeferenced registration and control of water users. The GIS environment includes tools for data mining and integrating the NGFlow and QUAL2E models for river runoff and water quality simulation; these tools were successfully validated in the Cuiabá River basin. To guarantee acceptance and continuity of system maintenance in regions under development, GIS applications for watershed management should be component-based. They should also integrate models with robustness for input data that are poor in consistency and quality. Finally, they should be implemented with development tools already used by local technical staff and have a high degree of user friendliness.